The Influence of Price Perception and Product Quality on Purchase Decisions Through Trust in the Furniture Business of PT Inti Sinergi Sistem, Bogor Regency - Syepi Hidayat; Hari Muharam; Yuary Farradia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine how price perception and product quality influence purchasing decisions through trust in the furniture business of PT Inti Sinergi Sistem in Bogor Regency. The sampling methods used were purposive sampling and simple random sampling by distributing questionnaires to 106 respondents using Google Forms. The data collected from the questionnaires were processed using SPSS Version 25 and Lisrel 8.80. The results of the study indicate that price perception and product quality influence consumer trust, price perception and product quality influence purchasing decisions, and consumer trust can act as a partial mediator between price perception and product quality on purchasing decisions in the furniture business of PT Inti Sinergi Sistem in Bogor Regency.